Effect of epitaxial crystallization on the structural evolution of PCL/RGO nanocomposites during stretching by in-situ synchrotron radiation. (20th December 2018) - Duan, Tianchen; Xu, Haojun; Tang, Yujing; Jin, Jing; Wang, Zongbao
Abstract: The effect of epitaxial crystallization on the structural evolution during the stretching process for PCL/RGO nanocomposites with different RGO content was investigated by in-situ WAXD and SAXS technique and ex-situ DSC and density measurements. WAXD results showed that the crystallinity and the degree of orientation for PCL/RGO nanocomposites changed less and slower after yielding with the increase of RGO content, especially comparing to that of pure PCL. SAXS results indicated that the long period increased before yield point and dropped after yielding and that the decrease of the long period after yielding changed slower with the increase of RGO content. DSC experiments revealed that the melting temperature after stretching was higher for PCL/RGO nanocomposites than pure PCL. Based on the results, PCL/RGO nanocomposites underwent strain-induced melting-recrystallization during the stretching process with relatively low velocity at room temperature and epitaxial crystallization had a restriction effect on the structural transformation of PCL. Graphical abstract: Highlights: The effect of epitaxial crystallization on the structural evolution for PCL/RGO nanocomposites was studied. The in-situ WAXD and SAXS techniques were used to study the structural evolution during the stretching process. PCL undergoes strain-induced melting-recrystallization during the stretching process with low velocity at room temperature. Epitaxial crystallization has a restriction effect on the structural transformation of PCL.